Case report: Fibroadenomas associated with atypical ductal hyperplasia and infiltrating epitheliosis mimicking invasive carcinoma - Wang, Li; Zhao, Wei; Zhou, Jue; Ge, Rong (Frontiers in Oncology, 2024)
Infiltrating epitheliosis (IE) is an uncommon type of complex sclerosing lesion in the breast. This condition is characterized by the infiltration of ducts into a scleroelastotic stroma, along with the presence of cells that display architectural and cytological patterns similar to those observed in usual ductal hyperplasia. We herein report a case of a 24-year-old woman who presented with bilateral breast nodules, which were initially identified as multiple fibroadenomas based on ultrasound findings. The patient underwent Mammotome system and regional mastectomy procedures, and subsequent pathological analysis confirmed the presence of multiple fibroadenomas with atypical ductal hyperplasia and infiltrating epitheliosis. This case discusses the challenges faced in diagnosing malignancy in a patient with multiple fibroadenomas accompanied by atypical ductal hyperplasia and infiltrating epitheliosis.